Glucocorticoids Regulate Circadian Rhythm of Innate and Adaptive Immunity - Shimba, Akihiro; Ikuta, Koichi (Frontiers in Immunology, 2020)
Animals have evolved circadian rhythms to adapt to the 24-hour day-night cycle. Circadian rhythms are controlled by the biological clock in the brain, which is driven by clock genes. Circadian rhythms are propagated from the brain to the periphery by nerves and hormones. Glucocorticoids (GCs) are a member of steroid hormones produced rhythmically by the adrenal cortex. GCs have both positive and negative effects on the immune system. Indeed, they are well known for their strong anti-inflammatory and immunosuppressive effects. Endogenous GCs inhibit the expression of inflammatory cytokines and chemokines at the active phase of mice, regulating the circadian rhythm of tissue inflammation. In addition, GCs induce the rhythmic expression of IL-7R and CXCR4 on T cells, which supports T cell maintenance and homing to lymphoid tissues. This T cell accumulation induces strong immune responses at the active phase. Clock genes and adrenergic neural activity control the T cell migration and immune response. On the other hand, other hormones produced at the rest phase enhance inflammatory cytokine expression. Taken together, circadian factors shape the diurnal oscillation of innate and adaptive immunity. Among them, GCs modulate the circadian rhythm of innate and adaptive immunity by positive and negative effects.